2002
DOI: 10.1046/j.1445-2197.2002.02590.x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery: The first 50 cases

Abstract: Transanal endoscopic microsurgery is an effective, safe and cost-beneficial procedure for local excision of selected lesions in the middle and upper thirds of the rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 14 publications
6
35
0
5
Order By: Relevance
“…The latter was a large series of 238 patients (226 patients treated by TEM and 12 by TE). It is remarkable that, with such high positive-residual-margin rates, the recurrence rates in these studies were only 5.6% after 33 mo follow-up [21] and 3.6% after 67.5 mo follow-up [38] , which are lower [14] 38 62 1 10 --1 Sutton et al [15] 60 102 4 -2 -0 Bujanda et al [16] 13 13 1 2 -15 (3-24) -Tsai et al [17] 131 …”
Section: Transanal Endoscopic Microsurgery (Tem)mentioning
confidence: 68%
See 1 more Smart Citation
“…The latter was a large series of 238 patients (226 patients treated by TEM and 12 by TE). It is remarkable that, with such high positive-residual-margin rates, the recurrence rates in these studies were only 5.6% after 33 mo follow-up [21] and 3.6% after 67.5 mo follow-up [38] , which are lower [14] 38 62 1 10 --1 Sutton et al [15] 60 102 4 -2 -0 Bujanda et al [16] 13 13 1 2 -15 (3-24) -Tsai et al [17] 131 …”
Section: Transanal Endoscopic Microsurgery (Tem)mentioning
confidence: 68%
“…In three large series, it has been found that adenoma recurrence rate is high in the incompletely resected group (37.7%, 46% and 25%) compared with that in patients with free histological margins after adenoma resection (4.3%, 3% and 3.7%, respectively) [28,33,34] . In another two studies, adenoma extending to the surgical margin of locally excised polyps was found in 25% [21] and 30.7% of cases [38] . The latter was a large series of 238 patients (226 patients treated by TEM and 12 by TE).…”
Section: Transanal Endoscopic Microsurgery (Tem)mentioning
confidence: 87%
“…Nevertheless, it has been proven to be cost-effective when compared to open resection in high volume centers, mainly driven by the shorter hospital stay. [5][6][7] The second rigid platform is the transanal endoscopic operation (TEO; Karl Storz, Tuttlingen, Germany). This less-expensive alternative allows surgeons to use standard laparoscopic instruments, including a 5 mm 30° laparoscope and overall laparoscopy setup, making this platform more affordable, and may be more attractive for surgeons with prior laparoscopic experience.…”
Section: Rigid Platformsmentioning
confidence: 99%
“…Complications TEM is usually a quick procedure with an average operating time around 67 minutes 12,28,34 . Complication rate is approximately around 10%, being fever, urinary retention, rectal bleeding and pain the most common.…”
Section: Carcinoid Tumormentioning
confidence: 99%
“…Rare complications are: abdominal perforation, transitory fecal incontinence and suture dehiscence with pelvic abscess. Few deaths are reported in the literature and most are in fact due to metastatic disease in the late postoperative or due to advanced disease in cases where palliative TEM was performed 12,13,14,27,30 . Both malignant and benign lesions have similar complication rates 14 .…”
Section: Carcinoid Tumormentioning
confidence: 99%